The Emergence of Similar Personalities in Similar Occupations - Claudia Rossetti; Torsten Biemann; Katja Dlouhy (Journal of Organizational Behavior, 2025)
Personality research suggests that individuals tend to develop more homogeneous—or similar—personalities within, rather than between, occupations due to attraction and selection, attrition, and socialization effects. We expand this perspective using a distance-based methodological approach that relates similarities between combinations of individuals' personality traits to similarities between their occupations. Leveraging German panel data tracing individuals' careers from 2005 to 2017, we test how attraction and selection, attrition, and socialization effects contribute to the emergence of similar personalities in similar occupations over time. Our results reveal that individuals with more similar Big Five personality traits join more similar occupations, whereas those with personalities less similar to those of other occupational incumbents are more likely to leave the occupation. Moreover, individuals staying in more similar occupations develop more similar personalities. These findings enhance our understanding of the intricate interplay between individuals' personalities and occupations, providing evidence that similar personality traits emerge not only within the same occupation but also between similar occupations over time.
Keywords: 650; homogeneity; occupation; personality; person–environment fit; similarity